Trade growth and poverty: A case of Pakistan - Rana Ejaz Ali Khan; Rashid Sattar (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
It is generally argued that open trade is crucial for economic growth and development. The economic literature also argues that growth is an important option for reducing poverty in developing countries. The paper analyzed the causality between the trade, growth and poverty for Pakistan using annual time series data from 1973-2009. Granger causality results based on Error-Correction Models have shown that in the case of Pakistan there exists two way relationship between trade and growth in the long-run but for the short-run growth enhance the trade. For the growth and poverty, there exists long-run relation from growth to poverty while for the short-run there exists no relationship. It may be concluded that international trade can play an important role towards growth and ultimately alleviation of poverty. From the policy perspective government should focus on trade.
Keywords: 330; Trade Openness; Economic Growth; Poverty; Error-correction Model; Pakistan